Quantification of HEV RNA by Droplet Digital PCR - Florence Nicot; Michelle Cazabat; Sébastien Lhomme; Olivier Marion; Karine Sauné; Julie Chiabrando; Martine Dubois; Nassim Kamar; Florence Abravanel; Jacques Izopet (Viruses, 2016)
The sensitivity of real-time PCR for hepatitis E virus (HEV) RNA quantification differs greatly among techniques. Standardized tools that measure the real quantity of virus are needed. We assessed the performance of a reverse transcription droplet digital PCR (RT-ddPCR) assay that gives absolute quantities of HEV RNA. Analytical and clinical validation was done on HEV genotypes 1, 3 and 4, and was based on open reading frame (ORF)3 amplification. The within-run and between-run reproducibilities were very good, the analytical sensitivity was 80 HEV RNA international units (IU)/mL and linearities of HEV genotype 1, 3 and 4 were very similar. Clinical validation based on 45 samples of genotype 1, 3 or 4 gave results that correlated well with a validated reverse transcription quantitative PCR (RT-qPCR) assay (Spearman rs = 0.89, p < 0.0001). The RT-ddPCR assay is a sensitive method and could be a promising tool for standardizing HEV RNA quantification in various sample types.